Inherited Spouses or Negotiated Existence? Agency of Women, Authority, and Levirate Matrimony - ABD Faiz Karim; Wahidin; Zulfahmi AR (LPPM IAIN Parepare, 2026)
Levirate marriage has historically served as a means of maintaining family continuity and supporting widows in many traditional societies. However, little is known about how women experience and respond to this practice in Eastern Indonesia, particularly in Sumba. This study examines women’s experiences of levirate marriage and the ways they navigate customary expectations and family obligations. Using a qualitative approach, data were collected through in-depth interviews, 24 sessions of participant observation, and document analysis involving widows, family members, and 4 adat leaders. The findings show that levirate marriage provides social acceptance, economic support, and access to family resources for widows. At the same time, customary norms and family expectations often limit women’s ability to make independent decisions regarding remarriage and residence. Women responded to these conditions in different ways, including accepting the arrangement for economic security, negotiating the timing of decisions, and selectively resisting family demands. These findings suggest that levirate marriage involves both support and constraint, shaped by ongoing interactions between women, families, and customary institutions. The study contributes empirical evidence from Sumba and highlights the importance of strengthening women’s participation in decisions affecting their lives.